KEPUASAN MASYARAKAT PENERIMA BANTUAN PKH TERHADAP KINERJA PENDAMPING DI PAWOH KECAMATAN SUSOH, ACEH BARAT DAYA - Muspida Muspida; Triyanto Triyanto (Jurnal Society : Pengamat Perubahan Sosial, 2023)
This research is motivated based on observations in the field on the assisting process carried out by PKH assistants in providing services, the way services are provided to the community and measuring the level of community satisfaction with the performance of companions. The purpose of this study is to determine the level of satisfaction of the PKH beneficiaries with the performance of PKH assistants in Gampong Pawoh, Susoh District. The sample collection technique used by the researcher was a systematic random sample (Syistematic Random Sampling), thus the sample in this study amounted to 50 respondents where data collection was collected by filling out a questionnaire, then the data collection technique was carried out through literature studies and field studies which included: Observations and questionnaires. From the results of the study, it can be concluded that public satisfaction with the performance of PKH assistants is quite satisfactory and maximally realized, the performance of companions who have provided the best possible services but which is an obstacle in mentoring, there is still a lack of desire from some KPM to attend PKH meeting activities, there is still a lack of understanding in the digestion of information or learning provided by the companion, and some activities carried out in supporting  assistance duties so that there are often miscommunications, especially information about PKH to the beneficiary community in Gampong Pawoh with companions so that many of the KPM come to see the PKH coordinator at the Abdya Social Service.Keywords: Family Hope Program (PKH). PKH Companion. Community Satisfaction.